PERANAN PROKALSITONIN PADA PNEUMONIA KOMUNITAS - Mirza Purwitasari; Erlina Burhan; Priyanti Z. Soepandi (The Indonesian Journal of Infectious Diseases, 2015)
Abstrak : Keterbatasan dalam mendiagnosis infeksi respirasi dari klinis, gejala penyakit dan pemeriksaan mikrobiologis, keberadaan biomarker dapat dijadikan informasi tambahan dalam meningkatkan diagnosis dan prognosis yang membantu dalam keputusan pemberian terapi. Penggunaan prokalsitonin dapat membantu diagnosis membedakan dari infeksi yang disebabkan oleh virus, menilai derajat risiko pasien dan keputusan pemberian, penghentian dan durasi antibiotik yang optimal. Pneumonia komunitas masih menjadi masalah kesehatan. Prokalsitonin pada akhir-akhir ini menjadi perhatian prognosis pada pneumonia komunitas. , baik yang diakibatkan oleh bakter iatau pun bukan. Prokalsitonin juga mempunyai kemampuan yang lebih baik dari pada C-reaktif protein sebagai biomarker petanda inflamasi dan mempunyai hubungan yang signifikan dengan skor sistem yang menilai klinis dan angka kematian. Kata kunci: Pneumonia komunitas, prokalsitoninAbstract : In light of the limitations of clinical signs and symptoms and traditional microbiologic diagnostic for respiratory infections, blood biomarkers that correlate with the presence and extent of bacterial infections may provide additional useful information to improve diagnostic and prognostic efforts and help with therapeutic decisions in individual patients. A growing body of evidence support the use of procalcitonin (PCT) to differentiate bacterial from viral respiratory diagnoses, to help risk stratify patients, and to guide antibiotic therapy decisions about initial need for, and optimal duration of, therapy.Communityacquired peneumonia (CAP) is a significant clinical and public health problem. Recently, attention has been paid to the potential for procalcitonin (PCT) both to differentiate the diagnosis and to indicate the prognosis of pneumonia. Procalsitonin has the ability to supplement clinical information to determine whether or not the cause of the inection is likely to be bacterial. In addition, PCT seems to be superior to the most prevalent inflammatory biomarker C-reactive protein a